THE INDONESIAN GOVERNMENT'S POLICY IN IMPROVING THE TEACHERS' QUALITY OF ELEMENTARY SCHOOL - Sunarti, Sunarti (Nurul Jadid University, 2022)
Teachers occupy a central position and are essential components in the education system. Thus, the government must pay great attention to the professional qualifications of teachers. This study aims to understand government policies for improving the quality of teachers. This study uses a mixed-method approach by combining qualitative and quantitative approaches. The population of this study was all teachers in Tanah Datar Regency, West Sumatra. While the samples used were teachers at SDN 001 Lima Kaum District, SD 07 Sungai Jambu Pariangan District, SDN 01 Gurun Sungai Tarab District, and SDN 03 Rambatan, Rambatan District. The research results found that the professional teacher quality level was still quite good. The results also show that the level of professional quality of teachers is still quite good. Efforts made by the government through its policies are carried out through; increasing teacher salaries and welfare, establishing a certification system for educators and education personnel, an education quality assurance system, and establishing professional working groups.